Characterization of wastewater-derived bacteriophages infecting Enterococcus faecalis in Bulgaria: insights into the novel phage vB_SEF_8 - Kizheva, Yoana; Dimova, Tsveta; Pandova, Maria; Gladicheva, Yoana; Petrova, Ralitsa; Paunova-Krasteva, Tsvetelina; Urshev, Zoltan; Ivanov, Sergei; Hristova, Petya (Frontiers in Microbiology, 2025)
Enterococcus faecalis is an opportunistic pathogen associated with nosocomial infections, food spoilage, and reduced efficacy of orally administered medications in patients with Parkinson’s disease. Its genetic adaptability, particularly in acquiring virulence and antibiotic resistance genes, poses a significant challenge in treatment. Тhus, the development of new and effective approaches, such as phage therapy, is crucial in the fight against E. faecalis. The main goal of this study was to establish the biological characteristics of three bacteriophages (designated as vB_SEF_8, vB_SEF_13 and vB_SEF_15) isolated from wastewater in Bulgaria and their potential to eliminate E. faecalis. The host ranges of the phages were determined primarily using E. faecalis strains (n = 29), although other species within the genus Enterococcus were also included. All three phages targeted only E. faecalis strains, including antibiotic-resistant or multidrug-resistant strains. The phages showed broad pH (4.0–10.5) and temperature (up to 80 °C) stability, formed clear plaques, with maximal titers reached at various MOIs. After 9 months at 4 °C, only a slight titer reduction was observed (up to 2 log10 PFU/mL). RFLP analysis revealed genetic diversity among the three phage isolates. The phage with the broadest host range (vB_SEF_8) was characterized in more details. TEM observation revealed elongated head and long noncontractile tail. vB_SEF_8 possessed linear dsDNA and lacked genes associated with lysogeny, antibiotic resistance, or virulence. Phylogenetic analysis and the calculated pairwise intergenomic distance showed that vB_SEF_8 is a novel species within the Saphexavirus genus, class Caudoviricetes. The phage also successfully inhibited E. faecalis in a milk-based matrix. The collected data demonstrate that vB_SEF_8 holds significant potential as an antibacterial and therapeutic agent against E. faecalis in settings where the presence of this bacterium is undesirable.